Effect of surface modification of SiO2@TiO2 core–shell particles on the structural colour under an electric field. Issue 9 (23rd December 2014) - Qiao, Xuanxuan; Luo, Yuxia; Sun, Aihua; Wang, Chongyang; Zhang, Jianfei; Chu, Chengyi; Guo, Jianjun; Xu, Gaojie
Abstract : Surface modified colloidal SiO2 @TiO2 core–shell particles were chosen to study their responsive photonic properties and the effect of surface on structural colour under low electric field. Abstract : Surface modified colloidal SiO2 @TiO2 core–shell particles were chosen to study their responsive photonic properties and the effect of surface on structural colour under low electric field. The surface of SiO2 @TiO2 core–shell particles was controllably coated by PDDA, PVA and SiO2 . A corresponding colloidal suspension of the modified SiO2 @TiO2 showed completely different reflection spectra. The dielectric spectrum was employed to explain the effect of surface properties on the assembly.